STUDENTSâ€™ PERCEPTIONS AND ATTITUDES TOWARDS THE LEARNING OF GLOBAL ISSUES VOCABULARY USING COOPERATIVE LEARNING METHODS - Lamis Abdulkarim Al-Shuga’a; Kamariah Yunus (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
As a matter of fact, the cooperative learning method is considered one of the most effective student-centered learning methods used in teaching English language classes. It is an updated and effective pedagogic method that should be incorporated in classrooms. The previously reviewed studies showed that group work is better than individual work since student-centered learning methods may improve studentsâ€™ knowledge of the language because of their effective cooperative engagement. This paper aims at investigating students’ perceptions and attitudes towards the learning of global issues vocabulary using cooperative learning methods. The study employed a survey method research design where the quantitative data collection method was conducted. 25 participants are subjected to the intervention phase for seven weeks (40 hours) at MALI institute in Taiz, Yemen. Then a well-prepared questionnaire was conducted on the participants within a period of two days, immediately after the intervention phase. The descriptive statistic SPSS (Statistical Package for Social Sciences) version 25.0 was used to analyze data. Percentages were used for the questionnaire. The results from the questionnaire indicated that cooperative learning techniques had positive effects on studentsâ€™ writing in classrooms. The participants gained confidence and their language skills were improved. Social skills like leadership, decision-making, trust-building, communication, and conflict-management skills were also developed. The study concludes that cooperative learning contributes to cognitive growth, increased autonomy, and productivity. The cooperative learning method should be integrated into English language classrooms to improve the growth and productive knowledge of students.